Melatonin mediates seasonal transitions in aggressive behavior and circulating androgen profiles in male Siberian hamsters - Munley, Kathleen M. (Horm Behav, 2019)
Some seasonally-breeding animals are more aggressive during the short, “winter-like” days (SD) of the non-breeding season, despite gonadal regression and reduced circulating androgen levels. While the mechanisms underlying SD increases in aggression are not well understood, previous work from our lab suggests that pineal melatonin (MEL) and the adrenal androgen dehydroepiandrosterone (DHEA) are important in facilitating non-breeding aggression in Siberian hamsters (Phodopus sungorus). To characterize the role of MEL in modulating seasonal transitions in aggressive behavior, we housed male hamsters in long days (LD) or SD, treated them with timed MEL (M) or saline injections, and measured aggression after 3, 6, and 9 weeks. Furthermore, to assess whether MEL mediates seasonal shifts in gonadal and adrenal androgen synthesis, serum testosterone (T) and DHEA concentrations were quantified 36 h before and immediately following an aggressive encounter. LD-M and SD males exhibited similar physiological and behavioral responses to treatment. Specifically, both LD-M and SD males displayed higher levels of aggression than LD males and reduced circulating DHEA and T in response to an aggressive encounter, whereas LD males elevated circulating androgens. Interestingly, LD and SD males exhibited distinct relationships between circulating androgens and aggressive behavior, in which changes in serum T following an aggressive interaction (ΔT) were negatively correlated with aggression in LD males, while ΔDHEA was positively correlated with aggression in SD males. Collectively, these findings suggest that SD males transition from synthesis to metabolism of circulating androgens following an aggressive encounter, a mechanism that is modulated by MEL.